Securing password authentication using MD5 algorithm - Siti Nabilah , Mohammad Zain (2014)
Process of authentication can be defined as developing a unique mapping process from given password to some other unique information in a defined domain. This project is about to make sure that system integrity is secure by using cryptographic based encryption method.Multi —application usability of password today forcing users to have proper memory aids. Apart from protection, a step toward perfect security has taken by using MD5 algorithm